Hypoxic-ischemic brain damage of the fetus and newborn with hemodynamic disorders in the “mother-placenta-fetus” system - S. B. Berezhanskaya; M. К. Abduragimova (Медицинский вестник Юга России, 2023)
Objective: to identify the dependence of the severity of cerebral disorders in newborns and children of the first year of life on the indicators of blood flow in the utero-placental complex. Materials and methods: a total of 184 full-term newborns were examined in the period from birth to one year of life. The main group included children with cerebral ischemia of II and III severity and its consequences (group II, n=78; group III, n=42). Group I included newborns without signs of central nervous system damage, 14 of them had neurological symptoms by the end of the neonatal period (after a month, group I n =50, group II n =92). All children underwent general clinical examination, assessment of neurological status, ultrasound examination of the brain, transcranial dopplerography of cerebral vessels, electroencephalography. Maternal medical records were analyzed to identify hemodynamic parameters in the "mother-placenta-fetus" system at 12-13, 20-21, 28-32, and 36-40 weeks of gestation. Results: The features of uterine and fetal blood flow in the dynamics of gestation in mothers of the examined groups of children were determined. The associations between the values of Pi AUD, AUS, and AUM in the second and third trimesters of pregnancy in different groups were shown. The relationship between disorders of uteroplacental hemodynamics and the severity of cerebral pathology was revealed. A "method of antenatal prediction of the severity of cerebral disorders in newborns" was proposed. Conclusions: The obtained results make it possible to predict the risk of hypoxic-ischemic damage to the central nervous system in newborns antenatally using hemodynamic parameters in the mother-placenta-fetus system at 36 weeks of gestation.